A framework for dumping-based economies during the Covid-19 pandemic: A case of South African economy - Fotso, G. Bakam; Edoun, E.I.; Pradhan, A.; Sukdeo, N. (Technium Social Sciences Journal, 2022)
Maintaining economic supremacy has been a challenge for emerging countries due to the change in global outlook as imposed by the globalisation. Considering that the World Trade Organisation (WTO) refers to dumping as an economic approach to drive competitors for global market positioning, it is sometimes hard to prove since applying less price is a prerequisite market entry tactics only. Dumping-based economies are characterised by national practices and global influence that endanger local economic expansion such as more imports than exports, less protectionism practices, less foreign direct investment, unsuitable trade policies, less customer experience towards quality/price ratio and foreign exchange rate in addition to less government revenues. This study proposes a framework for dumping-based economies during the COVID-19 pandemic to guide nations towards economic development recovery. Transition economies should observe development of inclusive economies, corrective COVID-19 lockdown measures, convenient COVID-19 imports/exports regulations and sustainable anti-dumping measures to enhance domestic economies.